2021
DOI: 10.1080/09658211.2021.1895221
|View full text |Cite
|
Sign up to set email alerts
|

Effects of visual imagery on false memories in DRM and misinformation paradigms

Abstract: This study is an extension of recent research, which examined the possibility that false memories in the Deese-Roediger-McDermott (DRM) paradigm predict the occurrence of false memories in misinformation paradigm. The purpose was to determine in which extent an imaging instruction reduces false memories in DRM and Misinformation paradigms. A sample of young adults was assigned to the DRM or the misinformation tasks, either in control conditions or in conditions including an imaging instruction. Findings confir… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
(68 reference statements)
1
3
0
Order By: Relevance
“…Individuals with high visual imagery scores probably made visual mental images of the familiar words that were presented, thereby de-activating the brain regions usually recruited for verbal processing. This observation is compatible with studies which used the Deese–Roediger–McDermott paradigm and demonstrated that the instruction to form visual mental images of target words at encoding resulted in fewer false recognitions of non-target words 84 86 .…”
Section: Discussionsupporting
confidence: 89%
“…Individuals with high visual imagery scores probably made visual mental images of the familiar words that were presented, thereby de-activating the brain regions usually recruited for verbal processing. This observation is compatible with studies which used the Deese–Roediger–McDermott paradigm and demonstrated that the instruction to form visual mental images of target words at encoding resulted in fewer false recognitions of non-target words 84 86 .…”
Section: Discussionsupporting
confidence: 89%
“…It is well known that visual-motor imagery and enactment-encoding strategies increase correct memorization performances. In accordance with the distinctiveness heuristic hypothesis (Dodson & Schacter, 2001;Schacter, Israel, & Racine, 1999) explaining the effects of visual imagery encoding on DRM false memories (see Foley, 2012;Robin, Ménétrier, & Beffara-Bret, 2021), we expected that visual-motor imagery and enactment as encoding strategies compared to a control condition (listening to the action lists) should reduce false memories. Indeed, the distinctiveness heuristic hypothesis suggests that reductions in false recollection result from the monitoring decision based on a distinctive detail of the encoding context, which allows participants to decide whether an event has been previously experienced.…”
Section: Introductionmentioning
confidence: 57%
“…However, the results showed that enactment and visual-motor imagery did not reduce false memories, contrary to what was expected. These findings led us to question the classical models of memory which assume that the enactment effect and visual imagery favour distinctive conceptual processing to the detriment of relational processing, with the consequence of reducing false recognitions (see Foley, 2012;Goff & Roediger, 1998;Robin & Mahé, 2015;Robin et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation